On central extensions of Nulfilioform Leibniz algebras. - Sattarovich, Rakhimov Isamiddin; Langari, Seyed Jalal; Langari, Mouna Bibi (Hikari Ltd., 2009)
We establish a bijective correspondence between all central extensions of fixed Leibniz algebra L by V (with k−dimensional centers), and certain orbits in the set of all k−dimensional subspaces in the second cohomology group H2(L, V ), under the canonical action of Aut(L). As an application we describe the set of all nulfiliform Leibniz algebras.